Farmers' knowledge of The Implementation of GAP and Cattle-Palm Oil Integration toward Sustainable Agriculture - Bahtera, Novyandra Ilham; Yulia; Herza (JURNAL AGRICA, 2025)
The cultivation of oil palm has significantly increased in the Bangka Belitung Islands Province over the past decade, as farmers seek to improve their socioeconomic status. However, the agricultural practices of independent farmers often deviate from the desired standards. Implementing Good Agricultural Practices (GAP) in oil palm cultivation is crucial to optimizing farmers' efforts. This research evaluates farmers' understanding of GAP and the sustainable integration of cattle-palm oil cultivation. The study was conducted in Tiang Tara Village, using face-to-face interviews with independent farmers who own oil palm plantations. The findings revealed a significant lack of understanding among farmers regarding GAP and cattle-palm oil integration. Farmers continued to rely on traditional methods and the wisdom of experienced practitioners. At first, many were reluctant to adopt cattle-palm oil integration due to various constraints, including land scarcity, limited access to livestock grants, and insufficient knowledge of livestock management. The study recommends facilitating technology transfer from experienced farmers to their independent counterparts, increasing the dissemination of GAP knowledge by agricultural extension officers, and providing livestock grants along with intensive training and mentoring. These measures aim to promote sustainable integration of cattle-palm oil cultivation, enhancing both productivity and sustainability for independent farmers.